Social inequality in tooth loss, the mediating role of smoking and alcohol consumption. Issue 5 (20th May 2019) - Hach, Maria; Christensen, Lisa B.; Lange, Theis; Hvidtfeldt, Ulla A.; Danielsen, Bo; Diderichsen, Finn; Osler, Merete; Prescott, Eva; Andersen, Ingelise
Abstract: Objectives: The objective of the study was to investigate the mediated proportion of smoking and alcohol consumption in the association between education and tooth loss. Further, the objective was, on the additive scale, to decompose the total effect of education on tooth loss into the direct effect of education, the natural indirect effect through smoking and alcohol consumption (differential exposure) and the mediated interaction between education, smoking and alcohol consumption on tooth loss (differential susceptibility). Methods: The study was based on data from the Social Inequality in Cancer Cohort (SIC); a cohort constructed by seven pooled cohorts. The total study population comprised of 34 975 participants. With the use of natural effects models, we regarded smoking and alcohol consumption as intermediates; we investigated the role of smoking and alcohol consumption in mediating the effect of education on tooth loss. Results: In total, 4924 participants had tooth loss defined as <15 teeth present. The results of the analyses, on the additive scale, showed 1202 (95% CI: 623‐1781) additional persons with tooth loss per 10 000 persons among low compared to highly educated men. Among women, the analyses showed 1159 (95% CI: 959‐1359) additional persons with tooth loss per 10 000 persons. The results, on the relative scale, showed that 11% (95% CI: 8%‐15%) of the social inequality in tooth loss was jointly mediated by smoking and alcohol consumption among low‐educated men. Among women with low education, the mediated proportion was 26% (95% CI: 19%‐36%). Conclusion: Social inequality in tooth loss seems partly explained by differential exposure and differential susceptibility to smoking and alcohol consumption.